Market and design solutions to the short‐term economic impacts of marine reserves. Issue 4 (29th February 2016) - Ovando, Daniel; Dougherty, Dawn; Wilson, Jono R
Abstract: Well‐managed fisheries support healthy ocean ecosystems, coastal livelihoods and food security for millions of people. However, many communities lack the resources to implement effective fisheries management. No‐take marine reserves are a ubiquitous management intervention that provide conservation benefits and under certain circumstances can provide long‐term fishery benefits as a result of larval and adult emigration from reserve boundaries. But, support for marine reserves by fishery participants is often limited due to short‐term economic impacts resulting from foregone yields. In this study, we examine the timing and magnitude of economic impacts of marine reserves by utilizing a novel metric that discounts future economic benefits of enhanced productivity resulting from reserve protection. We ask under what circumstances long‐term benefits outweigh short‐term impacts of marine reserve implementation. We simulate fisheries for six species commonly caught in coastal environments and show that while conservation benefits accrue rapidly, more than a decade is often required to provide net fisheries benefits, even under circumstances favourable for reserves. We explore a suite of strategies for mitigating these short‐term economic losses, including flexible reserve designs, loans and enhanced ex‐vessel revenues. Results indicate that market‐based incentives show promise to offset short‐term economic losses. Our findings highlight the importance of understanding and communicating likely outcomes from marine reserve implementation and the need to engage supply chain actors to incentivize marine conservation that minimizes impacts to fishermen.